Analisa Efektifitas Kepusaan Penggunaan Aplikasi LARASKA ANRI Menggunakan Sistem Pengembangan Waterfall dan PIECES Framework - Muhammad Faiz Syafii; Iskandar Fitri; Rini Nuraini (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Family Archive Restoration Service (LARASKA) is a national archival institution that is present directly in the midst of people who have difficulty in handling community archives damaged by disasters. Since its launch in 2019, LARASKA has helped as many as 790 families and has repaired 33,193 archives. LARASKA ANRI is a service provided to the public free of charge by following established procedures. On February 21, 2021, exactly 1 day after the flood-hit Jabodetabek, the LARASKA ANRI team established a command post at the location to help people who have difficulty coming directly to ANRI. Thus, it is hoped that important public archives or documents as evidence of organizational accountability, both government and private, as well as evidence of community civil rights can be saved. The aim of the researchers from this study was to build a website-based LARASKA application to make it easier for the public to use the online application and conduct assessment analysis using the PIECES Framework.